Doctoral Creative Research on Innovation Vocal Method by Puntwitt - Asawadejmetakul, Puntwitt; Premananda, Weerachat; Thewtong, Duangjai (Rangsit Music Journal, 2025)
The Doctoral Creative Research on Innovation Vocal Method by Puntwitt represents a transformative effort in redefining the paradigms of vocal training and performance. This research is both conceptual and practical, aiming to introduce new perspectives in singing while addressing unexplored challenges in vocalization. By emphasizing the individuality of vocalists and their distinct physical attributes, the Method significantly reduces practice time while achieving remarkable improvements in vocal performance. Moreover, it expands traditional frameworks of physical and concept conditioning in singing, empowering singers to overcome both conceptual and physical limitations, thus unlocking their full potential. The research’s primary objectives are to create a personalized, systematic approach to singing that can serve as a universal guideline for training and teaching vocal techniques. Furthermore, it seeks to advance knowledge in 4 critical aspects of vocal production: respiratory mechanics, vocal fold functionality, tongue placement, and resonance control. These components are meticulously grounded in principles derived from vocal studies, scientific theories, and anatomical insights, offering a comprehensive foundation for its innovative approach. The research findings are presented through a lecture recital format, encompassing a lecture, solo vocal performances, choral singing, and staged excerpts from musicals and operas. The Method was studied and developed through extensive analysis of foundational vocal techniques, observations of master singers, and an in-depth study of the biomechanics of sound production. This included an exploration of principles such as sound generation, air pressure dynamics, and basic fluid mechanics. These insights were synthesized into a coherent framework, which was subsequently tested through experimental practice sessions with both the researcher and students at the Princess Galyani Vadhana Institute of Music. Participants included students majoring in vocal performance as well as those majoring in other instruments, ensuring the methodology’s adaptability across diverse musical disciplines. Before synthesizing into the researcher’s unique vocal methodology, the Method emphasized providing detailed explanations of interconnected mechanisms of organs and muscles involved in vocalization. Each section is presented through step-by-step explanation of interconnected functions of muscles and organs involved in singing. Each process is broken down into detailed segments, providing a logical and systematic approach to sound production while uncovering the intricate processes underlying the stages of vocal generation. The Method is a comprehensive approach to vocal training, meticulously structured around 4 core systems designed to enhance vocal efficiency, control, and resonance. These 4 systems work synergistically to refine the singer’s technique, allowing for sustainable vocal production and optimal sound quality: 1) the Reciprocal Breathing System: This technique refines breath control by synchronizing respiratory processes with the demands of vocal performance, ensuring efficiency and sustainability. 2) the Vocal Fold Functionality System: this system focuses on precise mechanics of vocal fold closure which is essential for creating a stable and resonant vocal tone. 3) the Tongue Placement System: by strategically positioning the tongue, this technique facilitates the creation of an air dam within the oral and pharyngeal cavities, optimizing airflow and enhancing vocal resonance. 4) the Resonance Collecting and Gathering System: this system explores methods for harnessing and amplifying natural vocal resonance, resulting in a fuller, more dynamic sound. The research also highlights the innovative nature of methodology, which challenges traditional paradigms of vocal training. By diverging from conventional approaches, the Method offers a more personalized and effective pathway for singers to achieve ultimate excellence. This Method was presented through a lecture recital, including solo vocal performances, choral works, and selections from musicals and operas, on January 16, 2025, at Sangita Vadhana Hall, Princess Galyani Vadhana Institute of Music. The presentation not only showcases the methodology’s practical applications but also provides an interactive platform for engaging with its theoretical foundations. The results demonstrate its potential to address the needs of singers across all genres, genders, and age groups. Furthermore, it provides a comprehensive framework for mastering vocal control, enabling performers to refine their technique in every dimension of artistry. In conclusion, the Method stands as a significant contribution to the field of vocal studies. Its holistic approach, combining theoretical rigor with practical application, offers a versatile and effective tool for singers and educators alike. By addressing both the conceptual and physical aspects of vocalization, it opens new avenues for artistic expression and technical mastery, ensuring its relevance and impact in the broader singing community. It is hoped that this research will generate a significant and lasting impact, with its flexibility enabling adaptation to a wide range of singers and repertoires. Moreover, it holds the potential to reshape the landscape of vocal education on a broader scale. Through the integration of interdisciplinary knowledge, this research aims to advance the field of vocal studies by introducing new perspectives. It is envisioned that this work will inspire a culture of continuous development in vocal performance and pedagogy in the future.